2018
DOI: 10.11118/actaun201866010325
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y Perceptions and Expectations of Food Quality Labels in the Czech Republic and Poland

Abstract: The paper advances the topic of food quality labels. The main goal of the study is to explore generation Y perceptions and expectations of food quality labels in the Czech Republic and Poland. The data were collected through an online survey from 372 respondents, involving 221 of Czechs and 151 of Poles. The statistical analysis procedures including descriptive statistics, Chi‑square test and Mann‑Whitney U test were performed to discover whether significant differences do exist between Czech and Polish consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The representatives of the small, medium, and large businesses expressed an opinion that the large number of food labels on the Czech market might be problematic (Figure 3), as suggested by Chalupová et al [30], Sadílek [4], and Velčovská and Hodra [33]. However, examining a possible correlation between whether the respondents were striving to obtain another label and what shortcomings they saw in the current labelling systems (Table 4), we found out that the food producers were inclined to apply for more labels, even though they saw some mild shortcomings in the food labelling systems they had joined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The representatives of the small, medium, and large businesses expressed an opinion that the large number of food labels on the Czech market might be problematic (Figure 3), as suggested by Chalupová et al [30], Sadílek [4], and Velčovská and Hodra [33]. However, examining a possible correlation between whether the respondents were striving to obtain another label and what shortcomings they saw in the current labelling systems (Table 4), we found out that the food producers were inclined to apply for more labels, even though they saw some mild shortcomings in the food labelling systems they had joined.…”
Section: Discussionmentioning
confidence: 99%
“…Czech food producers have reacted to the lasting trend on the market, increasing their interest in the labels that could become their competitive advantage [32]. However, Velčovská and Hadro [33], who compared respondents' perceptions and expectations of food quality labels in the Czech Republic and Poland, suggest that Czech consumers consider the number of food quality labels too high, finding them confusing. Consumers hence only pay limited attention to them when buying food [4,34].…”
Section: Introductionmentioning
confidence: 99%
“…A further proof stated by Velčovská and Hadro (2018), is given by the minimal labels' food quality awareness of consumers during grocery shopping.…”
Section: Differentiation Strategies From Food Mncs and Dual Quality Foodmentioning
confidence: 96%
“…Internationally, the origin of the product labeling can impact the perceptions of the consumers of every age group (Velčovská and Hadro 2018). It has been shown that country of origin effect varies with the consumers belonging to different countries (Insch and McBride 2004).…”
Section: Country Of Originmentioning
confidence: 99%